Taraxacum officinale (L.) Weber ex F.H. Wigg Root Extracts Inhibit the Growth of Bacterial Triggers of Selected Autoimmune Inflammatory Diseases and Potentiate the Activity of Conventional Antibiotics - Chen, Biao; Liu, Yelu; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: An increase in antibiotic resistance and a corresponding decrease in antimicrobial discovery have directed researchers towards alternative therapies, including plant-based medicines. However, synergistic combinations of plant extracts with conventional antibiotics may be a far more effective approach in overcoming resistance and potentiating the activity of antibiotics that are otherwise ineffective against resistant bacterial strains. Materials and Methods: The antibacterial activity of Taraxacum officinale (L.) Weber ex F.H. Wigg. root extracts was investigated by disc diffusion and quantified by liquid dilution and solid phase MIC assays against some bacterial triggers of autoimmune inflammatory diseases. The extracts were also combined with a range of conventional antibiotics and tested against various bacterial pathogens. The ΣFIC values obtained from these assays were used to determine the class of combinational effects. Toxicity was evaluated by Artemia nauplii mortality and HDF cytotoxicity assays. Results: Methanolic and ethyl acetate T. officinale root extracts showed good inhibitory activity against several microbial triggers of autoimmune inflammatory diseases, including P. mirabilis, P. vulgaris and A. baylyi. Of further interest, some combinations of the T. officinale root extracts and conventional antibiotics potentiated bacterial growth inhibition compared to the individual components alone. Six synergistic and seven additive interactions were noted. Additionally, two antagonistic interactions were evident, indicating that those combinations should be avoided. All extracts were nontoxic in the ALA and HDF assays, verifying their safety for therapeutic usage. Conclusion: Taraxacum officinale root extracts have potential as inhibitors of bacterial triggers of selected autoimmune inflammatory diseases. Furthermore, extract components may also potentiate the activity of three antibiotics that are relatively ineffective alone. Isolation and identification of these compounds may be beneficial in drug design against several bacteria, including the microbial triggers of rheumatoid arthritis and multiple sclerosis.
Keywords: Synergy; Conventional antimicrobials; Interaction; Medicinal plants; Rheumatoid arthritis; Ankylosing spondylitis; Multiple sclerosis; Drug combinations.